Ulasan Aspek Etnobotani dan Fitokimia pada Tumbuhan Andaliman (Zanthoxylum acanthopodium DC.) oleh Suku Batak Di Sumatera Utara - Bernadheta Rumondang Saragih; Reza Raihandhany (Pro-Life, 2023)
Andaliman (Zanthoxylum acanthopodium DC.) is an essential plant for the Batak people who utilize its fruit and seeds as spices for cooking, due to the tart taste. Apart of being food needs, andaliman is often used as a traditional medicine and traditional ceremonies. This research was conducted using a literature study method on various scientific using some keywords on the google scholar site. Aspects which were collected including the information on botany, ecology, distribution, local names, ethnobotany as local food and traditional medicine, and phytochemicals. Andaliman fruits and seeds are used as ingredients for cook such as arsik, sangsang, sup trites, gulai biawak, tasa telu, and kidu-kidu. In traditional medicine, andaliman is used to cure various diseases such as improving blood circulation, asthma, rheumatism, and increasing appetite. Besides for food and traditional medicine, andaliman can be utilized in agroforestry schemes as a plant to support natural environment conservation. Extract of andaliman fruit and seed contain various secondary metabolite chemical compounds, including alkaloids, flavonoids, glycosides, saponins, tannins, and triterpenoids. In the end, information on the utilization of andaliman becomes a consideration for maintaining its existence.